Proterozoic to Cretaceous evolution of the western and central Pearya Terrane (Canadian High Arctic). (October 2018) - Estrada, Solveig; Mende, Katja; Gerdes, Axel; Gärtner, Andreas; Hofmann, Mandy; Spiegel, Cornelia; Damaske, Detlef; Koglin, Nikola
Highlights: Pearya is a complex puzzle of crustal fragments with Grenvillian, Timanian, and Caledonian affinities. Pearya includes a Stenian-Tonian magmatic arc with 1000–950 Ma granitoids, intruded by mafic dykes at c. 600 Ma. Pearya includes an island arc formed at 500–470 Ma on a Timanian basement. Pearya was intruded by A-type granitoids at 486 Ma and charnockites at 460 Ma. After the accretion to Laurentia, Pearya was affected by Triassic/Jurassic and Cretaceous magmatism. Abstract: The Proterozoic to early Palaeozoic Pearya Terrane at the northern margin of Ellesmere Island is composed of several crustal fragments and is built up by five tectono-stratigraphic successions. This study focusses on parts of Successions 1–3 and related intrusions, including the Cape Fanshawe Martin Pluton (CFMP). Petrographical, geochemical, and geochronological data reveal a protracted, complex with in parts different geological history of these Pearya segments. Succession 1 is dominated by c. 1000–950 Ma old orthogneisses, which are part of a Stenian-Tonian magmatic arc. The arc was later intruded by mafic dykes probably related to the opening of the Iapetus Ocean. Post-tectonic leucogranite bodies were emplaced at c. 360 Ma. Succession 2 comprises Neoproterozoic to early Ordovician clastic sediments. It is subdivided in different units, for which the detrital zircon U–Pb ages reveal different source areas. Unit W with main ages at c. 1800–1050 Ma, and a youngest population at 1067 Ma, older than the biostratigraphic maximum depositional age of <600 Ma, was sourced from a continent that experienced the Grenvillian Orogeny. Unit A with ages mainly in the range of 1800–1000 Ma, and a maximum depositional age at 920 Ma, and Unit M2 with numerous age peaks between 2940 and 570 Ma and the maximum depositional age at 572 Ma received detritus from both the continental source and the Stenian-Tonian magmatic arc, and Unit M2 additionally from a Timanian island arc. Unit A was intruded by A-type granites at c. 485 Ma, which were migmatised at 454 Ma. The ultramafic to felsic CFMP at the coast of the Arctic Ocean northeast of Unit A comprises charnockites intruded at 458–456 Ma and granites emplaced at 441 Ma. The boundary with Unit A is probably tectonic. Succession 3 includes volcaniclastic sediments with detrital zircon ages of 621–492 Ma peaking at 573 Ma, which are dominantly sourced from an intra-oceanic Timanian island arc, and two genetically different igneous suites, an ophiolitic E-MORB suite of unknown age and a subduction-related suite formed at c. 500–470 Ma (Thores Suite). Both suites were juxtaposed during the M'Clintock Orogeny at c. 470–454 Ma. After the probably stepwise accretion of Pearya blocks to the northern margin of Laurentia during the Devonian to early Carboniferous Ellesmerian Orogeny, the Pearya Terrane was affected by thermal events during the Mesozoic, such as the intrusion of Triassic/Jurassic alkali-basaltic dykes and the Cretaceous magmatism of the High Arctic Large Igneous Province (HALIP). This study supports previous models that the Pearya Terrane is composed of crustal fragments, which are exotic to the Canadian Arctic margin.